Advances in the gut microbiome and mood disorders. Issue 1 (January 2023) - Mörkl, Sabrina; Butler, Mary I.; Lackner, Sonja
Abstract : Purpose of review: The gut microbiome is in constant bidirectional communication with the brain through the microbiota-gut-brain-axis. Mood disorders are among the most common psychiatric disorders and include major depressive disorder and bipolar disorder. The gut microbiome is altered in individuals with mood disorders and has a role in its inflammatory pathophysiology. In this article, we performed a narrative review of clinical studies, randomized controlled trials and meta-analyses addressing advances in gut microbiome research in mood disorders and included articles that were published between 2021 and 2022. Recent findings: Studies highlight transdiagnostic alterations of microbiota in mood disorders, with reductions of butyrate-producing bacteria. Participants with major depressive disorder showed altered beta-diversity, while participants with bipolar disorder showed reduced alpha-diversity. Both disorders exhibit alterations in the metabolome. Early pilot studies addressed the possibility of using the gut microbiome for the prediction of treatment response and the blood microbiome for the diagnosis of psychiatric disorders. Findings from clinical trials support the use of probiotics as an add-on therapy for major depressive disorder. The second published case report in the literature reported a favourable outcome of a patient with bipolar disorder after faecal microbiota transplantation. Summary: Gut microbiome modulations allow new treatment strategies including the use of psychobiotics for the treatment and prevention of mood disorders. Well designed clinical trials aiming for personalized medicine are needed to investigate the efficacy and safety of psychobiotic interventions.